Prognostic Significance of PNI in Patients With Pancreatic Head Cancer Undergoing Laparoscopic Pancreaticoduodenectomy - Jiang, Peng; Li, Xiaocheng; Wang, Shupeng; Liu, Yahui (Frontiers in Surgery, 2022)
Abstract Background: Recently, several prognosis indicators based on inflammatory and nutritional factors, such as neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte (LMR), plated-to-lymphocyte (PLR), and prognosis nutritional index (PNI) has been proposed as prognosis factors for several cancers, few reports have investigated PNI. The aim of this study was to investigate the prognostic significance of preoperative PNI in patients with pancreatic head cancer undergoing laparoscopic pancreaticoduodenectomy. Methods: Between February 11, 2018 to May 31, 2019, 251 consecutive patients with pancreatic head carcinoma were retrospectively recruited. The cut-off value was selected by receiver operator characteristic (ROC) curve. Patients were divided into a high PNI group (PNI>45.1) and a low PNI group (PNI<45.1), and clinic-pathological data was compared between the two groups. We evaluated the relationship between PNI and NLR, PLR, and LMR, and investigated their effect on overall survival. In addition, univariate and multivariate analyses were performed on the factors affecting the overall survival of patients. Results：Cut-off values of PNI, NLR, PLR and LMR were 3.7, 287.1 and 3.6, respectively. The low PNI group had significantly higher PLR and lower LMR between the two groups of patients. We found that PNI correlated negatively with PLR and NLR (r=-0.329, P<0.001 and r=0.170, P=0.014) but positively with LMR (r=0.476, P<0.001). Kaplan -Meier analysis suggested that the high PNI group was significantly better than the low PNI group (median survival days, 217 vs. 468, log-rank=45.92, P <0.001, FIG. 3A). Univariate analysis suggested PNI <45.1(HR: 0.357, 95%CI: 0.263-0.485, P<0.001) and LMR <3.6(HR: 0.705, 95% CI: 0.528-0.942, P<0.018) were found to be potential prognostic factors. Multivariate analysis suggested that only PNI <45.1 was an independent prognostic factor (HR: 0.359, 95%CI :0.256-0.502, P<0.001). Conclusions: Our study demonstrates that PNI is associated with various systemic inflammatory response marks and can be an independent prognostic factor for survival in patients with pancreatic head cancer.